Forming International Instrument Through One Health Approach for Health Justice - M Riadhussyah; Aisyah Wardatul Jannah; Basir, Salawati Mat; Subarkah, Alwafi Ridho (Magister of Law, Faculty of Law, University of Mataram, 2023)
Covid-19 is the proof that human health depends on animal and environmental health, these objects have interlinked with each other and provide impact to each other. Therefore, since international instruments have been formed, it will need the approach which is able to present these objects as the concerns to reach the global understanding on how to deal with pandemic situations, this is introduced through the one health approach for health justice, because disparities in COVID-19 infections, disease outcomes, and access to healthcare were stark and linked not only to health care system discrimination and inequality, but also to inequity throughout society. The purpose of this research is to discuss the importance of one health for health justice as the concept and approach to form international instruments. The method of this research uses qualitative methods and uses normative legal research or library research includes research on legal principles and this presents indirect data through scientific articles and books of the library conducted and supported with secondary and tertiary data. The discussion illustrates that one health as the approach which recognizes human, health and environment have bound each other and interlinked. Therefore, this approach will introduce the integration of interdisciplinary and cross-sectoral cooperation such as health diplomacy as a forum for negotiation between various states. In the end it shows that everyone may play an important role as the actor to promote the health of the populace in the future, one health concern will focus on zoonotic diseases, antimicrobial resistance, and food security for the future pandemic treaty. Health diplomacy through WHO can make a forum for International Health Regulations (IHR) requiring countries to designate a National IHR Focal Point.